2014
DOI: 10.1093/humrep/deu236
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance metabolomic profiling of Day 3 and 5 embryo culture medium does not predict pregnancy outcome in good prognosis patients: a prospective cohort study on single transferred embryos

Abstract: NCT01139268.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…Although promising, these approaches have still to consider the difficulties of their application on a daily/routine basis for assessing embryo competency. Alternative metabolomic approaches including nuclear magnetic resonance (NMR) and near-infrared spectroscopy (NIR) have not, to date, managed to successfully predict pregnancies (Hardarson et al 2012;Kirkegaard et al 2014).…”
Section: Metabolomics Of Spent Media and Reproductive Fluidsmentioning
confidence: 99%
“…Although promising, these approaches have still to consider the difficulties of their application on a daily/routine basis for assessing embryo competency. Alternative metabolomic approaches including nuclear magnetic resonance (NMR) and near-infrared spectroscopy (NIR) have not, to date, managed to successfully predict pregnancies (Hardarson et al 2012;Kirkegaard et al 2014).…”
Section: Metabolomics Of Spent Media and Reproductive Fluidsmentioning
confidence: 99%
“…A number of studies have attempted to non-invasively measure embryo quality based on the metabolic signatures of the embryo culture media by using a variety of techniques1617181920. Nonetheless, the extension of these findings to clinical application remains clouded by conflicting reports21 and technical complexities. Our group has demonstrated that uptake of pyruvate by the human embryos from culture medium and pyruvate to alanine ratio on day 3 of development is predictive of implantation potential20.…”
mentioning
confidence: 99%
“…More recently, a prospective cohort study analyzed the spent culture media on day-3 and on day-5 from 148 single transferred blastocysts. Despite of a high degree of individual metabolomic variation, no correlation was found with pregnancy outcome (49). On the contrary, a study performed on 621 frozen-thawed embryos transferred on day 4 revealed that metabolomic profiling of spent culture media is independent of morphology and correlates with implantation potential (50).…”
Section: Metabolomic Profilingmentioning
confidence: 96%